Cladribine (2-chlorodeoxyadenosine) in frontline chemotherapy for adult Langerhans cell histiocytosis: A single-center study of seven cases. (June 2013) - Adam, Zdeněk; Szturz, Petr; Vaníček, Jiří; Moulis, Mojmír; Pour, Luděk; Krejčí, Marta; Hájek, Roman; Mayer, Jiří
Abstract Background. Adult Langerhans cell histiocytosis is a rare disorder with diverse clinical manifestations and inconsistent treatment outcomes to conventional therapeutic regimens. Cladribine (2-chlorodeoxyadenosine) repeatedly proved effective in cases of relapsed multifocal and multisystem disease forms. In this retrospective study we present an analysis of cladribine in frontline systemic therapy. Material and methods. A cohort of seven male patients with biopsy proved multisystem (six cases) and multifocal (one case) Langerhans cell histiocytosis received cladribine at a dose of 5 mg/m2 subcutaneously (five cases) or by two-hour intravenous infusion (two cases) over five consecutive days, every four weeks for a median of four courses (range 4–6). The treatment was enhanced with cyclophosphamide (300 mg intravenously on days 1–5 in cycles 4–6) and corticoids (dexamethasone 24 mg orally or methylprednisolone 250 mg intravenously on days 1–5 in cycles 4–6) in two patients, with radiotherapy (20 Gy on skin or bone lesions) in three patients and with photochemotherapy (psoralen plus ultraviolet A light, PUVA) on skin lesions in one patient. Results. All patients achieved clinically relevant treatment response confirmed by positron emission tomography (PET). Durable complete remissions were maintained in six patients (86%), including two patients with hypophysis involvement, with the median follow-up of 37 months (range 15–94; 49.8 ± 35.2 [6]). One patient had an aggressive, early relapsing disease requiring further treatment lines. The treatment-related toxicities consisted of transient bone marrow suppression affecting the leukocytes predominantly. Grade 3 lymphopenia occurred in five patients (71%) and grade 3 neutropenia in one patient (14%). Conclusion. Cladribine, both as a single agent as well as in combination with an alkylating cytostatic and corticoids, represents an effective treatment option with favorable toxicity profile for adult patients with multisystem or aggressive multifocal form of Langerhans cell histiocytosis.